Cross-cultural comparison of cultural mythologies and leadership patterns. Issue 1 (25th February 2014) - J. Wong-MingJi, Diana; H. Kessler, Eric; E. Khilji, Shaista; Gopalakrishnan, Shanthi
Abstract : Purpose: – The purpose of this paper is to explore leadership styles and patterns in India, Indonesia, Pakistan, and the USA in order to contribute to a greater understanding of global leadership. Design/methodology/approach: – The paper uses cultural mythologies as a lens (Kessler and Wong-MingJi, 2009a) to extract the most favored leadership traits within selected countries. In doing so, the paper explores historical trajectories and core values of each country to identify their distinctive characteristics. Additionally, leadership styles of well-known business leaders in each culture are examined to develop a comparative discussion of global leadership patterns and styles. Findings: – The paper finds that leaders may share same characteristics across countries, however, their behavioral expressions tend to unfold differently within each context. The paper argues that without context, meanings embedded in cultural mythologies and behaviors often become lost. The paper concludes that a comparative analysis of selected countries reveals a more complex and rich array of cultural meanings, thus offering support to a contextual view of leadership. Research limitations/implications: – Examination of cultural mythologies on leadership makes important theoretical contributions by illustrating that cultural mythologies indeed shape the values, behaviors, and attitudes of global leaders, and provide three important functions that are identified as: cultural bridging, meaning making, and contextual nuancing. Practical implications: – Understanding comparative leadership patterns is critical in international business. The paper offers cultural mythologies as a tool for leaders who seek to cross-cultural boundaries in developing long term and high-quality productive international business relationships. Originality/value: – The value of the study lies in developing a comparative analysis of leadership patterns in three Southeast Asian countries and the USA with the help of cultural mythologies. The paper urges that scholars to move beyond quantification of cultural dimensions to a more contextualized understanding of leadership.